Low energy availability - a study on the Black Ferns 7's rugby team - Kumar, J.; Black, K.; Baker, D.; Christensen, S.; Sharples, A.; Groom, J.; Sims, S (Sport and Exercise Science New Zealand Conference, 2018, 2018)
Low energy availability (LEA) has been described in various athletic populations however the prevalence amongst elite New Zealand female athletes is unknown. Methods: Informed voluntary consent was obtained from 23 contracted elite female rugby players who completed 5-day electronic diet records with the use of a smartphone application (MealLogger ©), and also completed the LEAF and a knowledge questionnaire. Results: Of the 23 participants (52.2%) of participants were classified as at risk of LEA. Those at risk had a lower median energy intake (28.7 kcal.kg-1.bw.d-1) compared to those not at risk (31.2 kcal.kg-1.bw.d-1). The mean knowledge score for those not at risk and those at risk was 5.5 and 4.9 respectively out of a potential score of 10. Further, 45.5% of those not at risk and 8.3% of those at risk, agreed that skipping periods make your bones weak. Discussion: The current study suggests that knowledge of LEA is low amongst elite athletes and that those who are at risk of LEA have poorer knowledge than those not at risk. This area requires further investigation as it is possible that educating athletes about LEA and its effects may reduce the number of athletes putting their health at risk.